Peran Kepuasan Kerja Terhadap Komitmen Organisasi dalam MSDM: A Systematic Literature Review - Imadianis Shafira Febylaila; Zuyyinna Choirunnisa (CV. ITTC INDONESIA, 2026)
Job satisfaction is a crucial factor in human resource management as it directly affects organizational commitment. This study aims to examine the influence of job satisfaction on organizational commitment using a Systematic Literature Review (SLR) approach. The review was conducted on nine scientific articles indexed in Scopus and SINTA by analyzing research variables, methods, sample characteristics, and key findings. The results indicate that job satisfaction significantly enhances organizational commitment, particularly through interpersonal relationships, leadership quality, job security, recognition, and career development opportunities. Furthermore, job satisfaction functions as a mediating variable between human resource management practices and organizational commitment. These findings highlight the importance of implementing supportive leadership and humanistic HR policies to strengthen employee attachment and loyalty to organizations. This study provides theoretical and practical insights for developing effective human resource strategies that promote employee well-being and sustainable organizational performance.